The green road [large type] - Enright, Anne, 1962- (Thorndike Press, a part of Gale, Cengage Learning, 2015)
Ardeevin, County Clare, Ireland. 1980. When her oldest brother Dan announces he will enter the priesthood, young Hanna watches her mother howl in agony and retreat to her room. In the years that follow, the Madigan children leave one by one: Dan, not a priest, for the frenzy of New York under the shadow of AIDS; Constance for a hospital in Limerick, where petty antics follow simple tragedy; Emmet for the backlands of Mali, where he learns the fragility of love and order; and Hanna for modern-day Dublin and the trials of her own motherhood. When Christmas Day reunites the children under one roof, each confronts the terrible weight of family ties and the journey that brought them home.